Influencing analysis of different baffle factors on oil liquid sloshing in automobile fuel tank. (November 2020) - Zhang, Enhui; Zhu, Wenyan; Wang, Lihe
Oil liquid sloshing is a common phenomenon in automobile fuel tank under variable working conditions. Installing baffles in automobile fuel tank is the most effective way to suppress adverse influence caused by oil liquid sloshing. Different types of three-dimensional finite element models filling oil liquid are created, meshed, and simulated. The reliability of simulation results is verified by test. The concept of time–area value is proposed in this work. In order to explore the influence of different baffle factors on oil liquid sloshing, six factors are studied. Six kinds of influencing factors are height, structure, shape, spacing, number, and placement of baffles. The sloshing pressure and time–area value are the core parameters for evaluating the influence degree. Some results could be obtained by comparing the parameters of oil liquid sloshing under the same condition. High baffles and baffles with small spacing have obvious attenuation influence on the pressure of oil liquid sloshing. Low baffles, double baffles, parallel baffles, and the combined action of inertia force and gravity are more beneficial to the reduction of time–area value. Time–area value is the largest and the smallest in fuel tank with intersection baffles and low baffles, respectively.